2013
DOI: 10.1039/c3tb20786b
|View full text |Cite
|
Sign up to set email alerts
|

Nanolayered chemical modification of silicon surfaces with ionizable surface groups for pH-triggered protein adsorption and release: application to microneedles

Abstract: The aim of this work was to develop a nanolayered pH sensitive coating method whereby proteins are coated at a suitable pH on the surface of chemically modified biomedical/bioanalytical microdevices and protein release is triggered by a pH-shift upon contact with the physiological environment. In this work such a coating was developed and was applied onto microneedles. First, the surface of microneedle arrays was modified with basic groups with a surface pK a below physiological pH. This modification was a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
(48 reference statements)
3
29
0
Order By: Relevance
“…First, the pH-sensitive pyridine-modified microneedle arrays were prepared as described previously (6). The microneedle arrays were coated with LB-MSN-OVA at pH 5.8 in an EDTA buffer (1 mM).…”
Section: Resultsmentioning
confidence: 99%
“…First, the pH-sensitive pyridine-modified microneedle arrays were prepared as described previously (6). The microneedle arrays were coated with LB-MSN-OVA at pH 5.8 in an EDTA buffer (1 mM).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the kinetics of insulin delivery to mice from dissolving MNs has also been shown to be comparable to subcutaneous injection [42]. Addressing the issue of what can be coated onto MNs, other studies have examined coating formulations to deliver the model proteins bovine pancreatic ribonuclease A (13.7 kDa) and chicken ovalbumin (45 kDa) [72], [73]. Both studies found that the model proteins could be delivered into skin in vitro , with dosage and release kinetics dependent on the coating chemistry.…”
Section: Areas Of Potential Impactmentioning
confidence: 99%
“…pH-sensitive surface modification was also reported in the fabrication of pH-sensitive microneedles. Here, MNs were coated with ovalbumin, a model antigen, and a pH-sensitive pyridine surface [24]. Upon insertion into the acidic skin conditions, reduced electrostatic interactions allowed the ovalbumin to be efficiently released.…”
Section: Ph-responsive Transdermal Patchesmentioning
confidence: 99%